The description of Kabarda by D.A. Milutin in the context of the cauсasus version of russian orientalism foundation. - Dmitrii Tkachenko (Кавказология)
The paper pertains to the analysis of a manuscript authored by D.A. Milutin in the first half of the 19th century, regarding the region of Kabarda. This manuscript, hitherto unpublished in academic circles, has been the subject of our examination. Our endeavor was to uncover the utilization of orientalist clichés by the manuscript's author, in order to depict both the geographical delineations of this ethno-political entity and the ethnography, livelihood, societal structure, and customary legal norms of its inhabitants. A remarkable parallel can be observed between certain aspects of the manuscript and the ideas propounded by E. Said in his discourse on European Orientalism. The researcher drew a comparison between the political framework and traditions of the Kabardian people and those prevalent in Europe. Moreover, the researcher romanticized the region's historical past, employing the conceptof "reverse human progress," along with other typical methodologies embraced by Orientalist thinkers of that era. Concomitantly, D.A. Milutin provided detailed descriptions of the political, social, and everyday existence in Kabarda, thereby endowing the manuscript with an intrinsic value as an original historical and cultural resource for contemporary scholars. It is concluded that, similar to numerous analogous texts produced by Orientalist scholars, the significance of D.A. Milutin's man-uscript lies not in its political arguments concerning the military and economic dominion of the Russian Empire over the Caucasian peoples, or the imperative to extend colonial governance to these ethnic territories